2015
DOI: 10.3389/fphar.2015.00247
|View full text |Cite
|
Sign up to set email alerts
|

HDL as a drug and nucleic acid delivery vehicle

Abstract: This review is intended to evaluate the research findings and potential clinical applications of drug transport systems, developed based on the concepts of the structure/function and physiological role(s) of high density lipoprotein type nanoparticles. These macromolecules provide targeted transport of cholesteryl esters (a highly lipophilic payload) in their natural/physiological environment. The ability to accommodate highly water insoluble constituents in their core regions enables High density lipoproteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…The drugs physically loaded into HDL nanoparticles were primarily taken up under the regulation of SRB1 receptors and subsequently directly delivered into cytoplasm. 34,54 Alternatively, as shown in Figure 5, the drugs electrostatically interacted with HDL-lipid layers and preferred to enter cells following the endocytosis of whole nanoparticles, which was in accord with our previous report. 35 This uptake pattern of HMNs has been discovered to be mediated by a cluster of proteins, including the ectopic β-chain of ATP synthase and P2Y13 receptors; 55 nevertheless, the exact mechanism is still under study.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The drugs physically loaded into HDL nanoparticles were primarily taken up under the regulation of SRB1 receptors and subsequently directly delivered into cytoplasm. 34,54 Alternatively, as shown in Figure 5, the drugs electrostatically interacted with HDL-lipid layers and preferred to enter cells following the endocytosis of whole nanoparticles, which was in accord with our previous report. 35 This uptake pattern of HMNs has been discovered to be mediated by a cluster of proteins, including the ectopic β-chain of ATP synthase and P2Y13 receptors; 55 nevertheless, the exact mechanism is still under study.…”
supporting
confidence: 80%
“…[32][33][34][35] Furthermore, HDL plays a crucial role in the reverse cholesterol-transport process, acting as a vehicle that transports cholesterols to a variety of organs for metabolism. [36][37][38] It is worth mentioning that cholesterol is an essential element to form cell membranes.…”
mentioning
confidence: 99%
“…Advances in nanotechnology and using targeted drug delivery vehicles, have shown great potential to overcome these challenges to effective chemotherapy. The therapeutic index of a drug can be significantly improved by increasing the preferential accumulation of the therapeutic agent in malignant cells while protecting healthy cells and thereby reducing toxic side effects (Rigotti et al, 2003; Foit et al, 2015; Lacko et al, 2015). …”
Section: Cancer Therapeutics: Challenges and Novel Therapiesmentioning
confidence: 99%
“…In order to overcome systemic toxicity caused by drug administration, Doxorubicin can be administered instead as a molecular theranostic agent with targeted delivery to Scavenger receptors type B1 (SR-B1) overexpressed in tumors; by encapsulation in reconstituted high density lipoprotein (rHDL) nanoparticles. Recent research has indicated the possibility of using nanoparticles to avoid systemic toxicity and achieve targeted drug delivery [8,9,1115]. Thus, using nanotechnology and chemistry, it is possible to reduce the systemic toxicity and produce targeted drug delivery, and track these changes using fluorescence.…”
Section: Introductionmentioning
confidence: 99%